SIFAT KIMIA TEPUNG JAGUNG LOKAL PUTIH TIMOR TERMODIFIKASI MELALUI FERMENTASI BAKTERI Lactobacillus casei - Maria Susana Medho; Abdul Kadir Djaelani; Bachtaruddin Badewi (Partner, 2018)
The characteristics of flour much determine the quality of food products. Maize starch has several limitations to be developed into food products. Hence, to expand its use in food production, the starch needs to be modified. Modification of the starch can be done through the fermentation process. This modification is expected to change its physico-chemical aspects and functional properties. Some lactic acid bacteria (including L. bulgaricus and L.casei) are capable of degrading the corn cell wall,resulting in the starch granules to come out of the cell which eases the grinding process. L. bulgaricus and L. casei also can degrade starch contained in the growth medium into simple sugars, degrade proteins, and peptides into amino acids (Ganzle et al., 2008). The modified maize starch is also expected to be a proper substitution of regular flour in food products. The purpose of the research is to examine the quality of the modified starch through fermentation. The results showed that thefermentation time and concentration of bacteria dramatically affect the physical results where fermented corn was whiter and slightly acidic and chemically decreased the pH of corn flour to 4.5 and was relatively stable at 48 hours fermentation with a concentration of 4% and 6 %. The bestmodified chemical properties of local white corn are 36 hours fermentation with a concentration of 2% lactobacillus casei with a total protein value of 8.7%.